PWE-036 A significant proportion of patients attending colonoscopy have a poorly visualised colon segment with moviprep and this could be improved with preassessment – results of a 'real world' audit using boston bowel preparation scale (bbps). (17th June 2017) - Robertson, J; Nylander, D
Abstract : Introduction: Bowel cleansing (prep) is an important aspect of colonoscopy. Better prep leads to more complete procedures, improved mucosal visualisation and detection of pathology. Previous reports have not used validated scoring systems to assess efficacy (1, 2). BBPS is validated and uses a visual scale of 0–3 to rate bowel cleansing in right, transverse and left colon segments; 0=inadequate, 1=poor, 3=excellent. A segment scoring 0 or 1 is deemed inadequately visualised for reliable diagnosis. Moviprep is main prep used for colonoscopy in our institution. We assessed efficacy of prep by carrying out a prospective audit using the BBPS. We particularly looked at 1. Patient tolerability 2. Effectiveness of bowel cleansing using BBPS 3. Effect of preassessment on compliance and effectiveness Method: All colonoscopists instructed on use of BBPS (a pilot audit had been done in 2015). The following data was recorded for all colonoscopies at our institution for 2 months starting 1/11/2016: Patient demographics, outpatient (OP) or inpatient (IP) status, timing of prep ingestion and BBPS for each of 3 colon segments. Data was entered on to spreadsheet by JR then analysed by DN Results: Data obtained from 537 procedures. Patient median age=60 (Range: 17–94). Caecum reached in 90% (in 3.9% failure to complete reported to be due to poor prep). 97% had OP prep. and 96% had Moviprep based prep (5.5% having additional Senna). 35 patients (7.9%) were unable to complete prep (18 –nausea/vomiting, 12-excessive volume). In 19%, there was at least 1 segment scoring 0 or 1 (no difference between AM and PM procedures). Pre-assessment did not significantly reduce no. of segments scoring 0 or 1 (16% if preassessed vs 20% if not; p=0.2). However patients who were not preassessed were significantly more likely not to complete their prep (9.8% vs 4.9% in preassessed) p=0.03. There were no recorded complications of Moviprep. Further data shown in table 1. Conclusion: 1. Moviprep is safe but a proportion of patients unable to complete current regime 2. 19% of patients have at least one inadequately visualised segment at colonoscopy 3. Completion of Moviprep regime significantly reduces proportion of patients with an inadequately visualised segment 4. Pre-assessment significantly improves proportion of patients who complete their Moviprep References: . Howells E. GUT2012. . Worthington J. Curr Med Res 2008. Disclosure of Interest: None Declared